Implantación de la contabilidad en el comercial Arévalo de la ciudad de Loja, periodo agosto – septiembre de 2014 - Cabrera Delgado, Cindy Mishel (2015)
This research paper is entitled: "IMPLEMENTATION OF ACCOUNTING IN THE COMMERCIAL AREVALO OF THE CITY OF LOJA, PERIOD AUGUST - SEPTEMBER 2014", is aimed at solving the lack of an accounting control has not allowed to know your real economic financial situation in the company under study and thus make the best decisions for business development based on their goals. Giving effect to the objectives in the research proceeded to perform the initial inventory through physical realization of values, assets and liabilities the company had at the beginning of the period for the registration of the account goods system was applied permanent or perpetual inventory account. State baseline followed by the entire accounting process was carried from the registry in the journal of all economic transactions, ledger, trial balance, worksheet until the financial statements: Statement of Financial Position, Income Statement and Cash Flow Statement as at 30 September 2014. Also was drawn assistants buying and selling goods for proper journal. At the end of this research accounting for Commercial Arevalo it was implemented, allowing real results that will help its owner to take decisions aimed at growth. Continue recommending accounting permanent system that will be an effective tool for organizing an enterprise accounts and also with the results obtained to evaluate the economic potential of the company.